A new species of Behningia Lestage, 1929 (Ephemerotera: Behningiidae) from China - Zhou, Xiongdong; Bisset, Mike; Xu, Mengzhen; Wang, Zhaoyin (Zootaxa, 2019)
A new species of sand-burrowing mayfly (Ephemeroptera: Behningiidae), Behningia nujiangensis Zhou & Bisset, is described based on more than 50 nymphs collected from the Nujiang River in Yunnan Province, P.R. China. This is the first species of the family Behningiidae discovered in China. It is also the second species of genus Behningia, and the third species of the family Behningiidae collected from the Oriental biogeographic region. The shapes of the labrum and the labium in B. nujiangensis are markedly different from those found in other species of Behningia. Differences in the mandibles, the galea-lacina of maxillae, and both the prothoracic and metathoracic legs differentiate B. nujiangensis from both B. baei and B. ulmeri. The biology of and conservation challenges for B. nujiangensis are also briefly discussed.